A avaliação e a sua relação com a saúde das pessoas afastadas do trabalho - Dourado, Amanda Dias (2020)
This dissertation corresponds to a qualitative study that sought as a general objective to investigate, through the speech of 9 workers away from work due to illness, the relationship between the operationalization of violent evaluative methods in the work context and the worker's health, and as specific objectives : analyze what happened to these workers while trying to achieve the results required in the work evaluation process while still active at work; understand the experiences of suffering arising from the evaluation process that has become a source of pathogenic suffering and investigate how these workers are experiencing the experience of breaking with work. The research was carried out at the Reference Center for Occupational Health - CEREST, in a capital city of Northeastern Brazil. To this end, a sociodemographic questionnaire and a semi-structured interview guided by the objectives of the study were used as an instrument. Data analysis took place through thematic content analysis with the theoretical help of Psychodynamics at Work. The results found for the proposed objectives were: the attempt to correspond to the high demands for results, often unattainable, is faced with the fragility of work groups and presenteeism. It was noticed that the suffering resulting from the evaluation process involves feelings of injustice, lack of recognition, unattainable goals, psychological pressure and humiliation in the exposure of the results. In the condition of being away, the workers revealed their discomfort due to their own pathology added to the feeling of uselessness and the shame of being sick.